2018
DOI: 10.1021/acs.jafc.8b05480
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Improves Barrier Function and Attenuates Inflammatory Responses in Porcine Intestinal Epithelial Cells during Lipopolysaccharide (LPS)-Induced Inflammation

Abstract: It is well known that essential oil thymol exhibits antibacterial activity. The 13 protective effects of thymol on pig intestine during inflammation is yet to be investigated. In this 14 study, an in vitro lipopolysaccharide (LPS)-induced inflammation model using IPEC-J2 cells was 15 established. Cells were pre-treated with thymol for 1 h and then exposed to LPS for various assays. 16 Interleukin 8 (IL-8) secretion, the mRNA abundance of cytokines, reactive oxygen species (ROS), 17 nutrient transporters, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 56 publications
(100 reference statements)
5
87
0
Order By: Relevance
“…Cells were seeded in twelve-well plate. When grown to confluence, 5 μM of LCA or dimethyl sulphoxide was used to treat cells for 12 h and then each well was added with LPS (10 μg/ml) or saline for another 4 h. The concentrations of LCA and LPS used were based on previous studies (22,23) . Cell culture medium was collected for measurement of IL-8.…”
Section: Determination Of Total Bile Acids Glucose and Glucagonlikementioning
confidence: 99%
“…Cells were seeded in twelve-well plate. When grown to confluence, 5 μM of LCA or dimethyl sulphoxide was used to treat cells for 12 h and then each well was added with LPS (10 μg/ml) or saline for another 4 h. The concentrations of LCA and LPS used were based on previous studies (22,23) . Cell culture medium was collected for measurement of IL-8.…”
Section: Determination Of Total Bile Acids Glucose and Glucagonlikementioning
confidence: 99%
“…Nutrient transporters are essential for gut homeostasis and proper absorption of nutrients. B 0 system neutral amino acid co-transporter 1 (B 0 AT1), system ASC sodium-dependent neutral amino acid exchanger 2 (ASCT2), apical sodium-dependent glucose transporter 1 (SGLT1), excitatory amino acid transporter 1 (EAAC1) and peptide transporter 1 (PepT1) are main nutrient transporters and chemosensing systems which are located on the apical side of IECs, and they play important roles in the transport of glucose, amino acids and peptides (Omonijo et al, 2019). Paracellular permeability is mainly regulated by tight junctions localized at the apical-lateral membranes to prevent leakage of macromolecules from the gut lumen (Laukoetter et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear why the gluco-conjugated form of thymol was unable to strengthen the GI integrity, especially because the luminal concentrations of both thymol and TαG in the distal jejunum were too low (<10 mg/kg) to be reliably detected with the current analytical method. Still, the effective thymol concentration needed to enhance the barrier function might be below our detection limit, as Omonijo et al (2019) [47] found already increased TEER values at only 50 µM or 7.5 mg/kg.…”
Section: Effects Of Thymol and Tαg Supplementation On The Intestinalmentioning
confidence: 73%
“…Unfortunately, no compositional analysis was performed for the colon. Otherwise, improved fecal scores potentially relate to the improved barrier function in the small intestine, which might indicate a reduced inflammatory status of thymol-supplemented pigs [47].…”
Section: Effect Of Thymol and Tαg Supplementation On Pig Performancementioning
confidence: 99%
See 1 more Smart Citation